PROBLEM BASED LEARNING IN TEACHING RECOUNT TEXT TO TENTH GRADE STUDENTS AT SMK NEGERI 1 DHARMA CARAKA GUNUNGSITOLI SELATAN - Hermin Gea; Yaredi Waruwu; Hidayati Daeli; Yasminar Amaerita Telaumbanua (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study is to analyze how the Problem Based Learning Implemented is applied when instructing tenth grade at SMK Negeri 1 Dharma Caraka Gunungsitoli Selatan in recount texts. The background of this study is the problem of students' low ability to write recount text correctly according to the structure of the text. Observation, interviews, test, and documentation were used to gather data for the descriptive qualitative study with research subjects of tenth grade students. The results show that students were more motivated and engaged when learning to write recount texts when the Problem Based Learning implemented was used. However, several students still had trouble accurately creating recount texts, especially when it came to language elements and organization. The study also showed that PBL promoted problem-solving, critical thinking and group collaboration in order to help students learn the subject matter. Students' limited language, time constraints, and inadequate comprehension of recall text structure were among the challenges faced. Overall, the PBL Model had a favorable impact on student results and the learning process, although ongoing teacher support is necessary to optimize students' writing abilities.